2008
DOI: 10.2174/1875044300801010040
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Signaling Strength Determines Target Gene Expression Profile in Human Keratinocytes

Abstract: Transforming Growth Factor-(TGF ) maintains keratinocyte homeostasis, and induces epithelial-tomesenchymal transition (EMT) in response to tissue injury. To investigate how these two TGF responses might become uncoupled during malignant transformation, we examined the TGF -regulated gene expression programs and cellular responses in human keratinocytes as a function of TGF type I receptor (T R-I) kinase activity and TGF level. The TGFmediated homeostatic gene response program and cellular growth arrest were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 54 publications
(85 reference statements)
1
16
0
Order By: Relevance
“…A key point is to distinguish between alterations in the level of TGFβ ligand and of the cellular components of the signaling separately. We have recently shown that these two variables have very different effects on the transcriptional profile of epithelial cells [67]. Our findings indicated that a quantitative reduction in the level of receptor expression or activity eliminates a set of genes from the TGFβ-regulated transcriptional program that are primarily involved in maintaining homeostasis and development.…”
Section: Tgfβ In Genetic Mouse Models Of Mammary Development and Cancermentioning
confidence: 78%
See 4 more Smart Citations
“…A key point is to distinguish between alterations in the level of TGFβ ligand and of the cellular components of the signaling separately. We have recently shown that these two variables have very different effects on the transcriptional profile of epithelial cells [67]. Our findings indicated that a quantitative reduction in the level of receptor expression or activity eliminates a set of genes from the TGFβ-regulated transcriptional program that are primarily involved in maintaining homeostasis and development.…”
Section: Tgfβ In Genetic Mouse Models Of Mammary Development and Cancermentioning
confidence: 78%
“…In the same set of MDA-MB-231-derived bone and soft tissue metastases, the expression of VEGF-A, -B, and -C was strongly up-regulated in the bone/bone marrow metastases compared to those in brain or lung. Importantly, VEGF is also a direct TGFβ target gene in epithelial cells [67]. Consistent with these observations, treatment of tumor bearing mice with the 2G7 anti-TGFβ neutralizing antibody significantly reduced circulating VEGF levels [112] (Genentech, US Patent Application 2005/0276802 A1).…”
Section: Alterations Of Tgfβ Signaling In Breast Cancer-loss Of Homeomentioning
confidence: 88%
See 3 more Smart Citations